Interactions one : (McGraw-Hill, 1997)
This manual provides instructions and guidelines for using the four texts separately or in various combinations to suit particular program needs. For each of the texts, there is a separate section with answer keys and teaching tips. There is also a midterm and final examination as well as a placement test for use with the entire Interactions program